Spatial distribution and trends of anemia among pregnant women in Ethiopia: EDHS 2005-2016 - Molla Abate Ayele; Haile Mekonnen Fenta; Dereje Tesfaye Zike; Lijalem Melie Tesfaw; Lijalem Melie Tesfaw (Frontiers Media S.A., 2023)
BackgroundAnemia is a public health problem affecting both developed and developing nations worldwide with a significant consequence on health and economic growth. The problem is more severe in pregnant women. Hence, the main purpose of this study was to determine the factors of anemia levels among pregnant women in zones in Ethiopia.MethodsWe utilized data from 2005, 2011, and 2016 Ethiopian demographic and health survey (EDHSs), a population-based cross-sectional study. The study includes 8,421 pregnant women. An ordinal logistic regression model with spatial analysis was used to explore factors of anemia levels among pregnant women.ResultAbout 224 (2.7%), 1,442 (17.2%), and 1,327 (15.8%) pregnant women were mild, moderate, and severely anemic, respectively. The spatial autocorrelation of anemia among the administrative zones of Ethiopia for the three consecutive was not significant. The middle wealth index of 15.9% (OR = 0.841, CI: 0.72-0.983) and richest wealth index of 51% (OR = 0.49, CI: 0.409-0.586) were less likely anemic compared to the poorest wealth index, age group of mother 30-39 was 42.9% (OR = 0.571, CI: 0.359-0.908) times less likely to be moderate and above anemic compared to <20 years, several household members 4-6 were 51% (OR = 1.51, CI: 1.175-1.94 more likely moderate and above anemic compared to 1-3.ConclusionOver one-third of the pregnant women (34.5%) were anemic in Ethiopia. Wealth index, age group, religion, region, number of household members, source of drinking water, and EDHS were significant factors in anemia levels. The prevalence of anemia among pregnant women varied among Ethiopian administrative zones. North West Tigray, Waghimra, Oromia special woreda, West shewa, and East shewa were a high prevalence of anemia.